2014
DOI: 10.1007/s11277-014-1874-0
|View full text |Cite
|
Sign up to set email alerts
|

A New Time-Domain Solution to Transmission Through a Multilayer Low-Loss Dielectric Wall Structure for UWB Signals

Abstract: In this work the time-domain solution for transmission through a multilayer wall structure has been presented. A time-domain transmission coefficient formulation for transmission through an interface between two low-loss dielectric mediums with different electrical properties is derived. Both hard and soft polarizations are considered. A novel ray tracing algorithm for multilayer wall structure has been presented with accuracy of ray-traced path as close as order of 10 −5 . Further, in depth formulation for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Figures and shows corner diffracted fields for dielectric 3D wedge and building, respectively, with dry concrete used as the lossy material. In building scenario, as the corner diffraction is associated with one corner and two edges, so the corner diffraction solution is applied twice, separate for each edge and then summed to get the total field strength at Rx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures and shows corner diffracted fields for dielectric 3D wedge and building, respectively, with dry concrete used as the lossy material. In building scenario, as the corner diffraction is associated with one corner and two edges, so the corner diffraction solution is applied twice, separate for each edge and then summed to get the total field strength at Rx.…”
Section: Resultsmentioning
confidence: 99%
“…This can be confirmed from (1), from where it is clearly observed that for parallel polarized component, field due to incident shadow boundary term and reflection shadow boundary term add in opposite phase while in case of perpendicular polarized component, they add in same phase thus increasing the field strength at Rx. Figures 4 and 5 shows corner diffracted fields for dielectric 3D wedge and building, respectively, with dry concrete [24] used as the lossy material. In building scenario, as the corner diffraction is associated with one corner and two edges, so the corner diffraction solution is applied twice, separate for each edge and then summed to get the total field strength at Rx.…”
Section: Resultsmentioning
confidence: 99%
“…s is the conductivity of the dielectric medium with 3 2 and 3 r2 as the dielectric permittivity and relative dielectric permittivity respectively. For loss-tangent much less than unity ðs=u3 < < 1Þ, the FD pathloss expression L total,s,h (u) for building scenario, is given as [14,15] (derived in the Appendix at the end of the paper)…”
Section: Formulationsmentioning
confidence: 99%
“…The TD solutions for transmission through a multilayer wall structure were presented in Ref. [14]. The TD solutions for transmission of UWB signals in microcellular and indoor scenario were presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It has some restriction in algorithm complexity for solving complex three‐dimension problems especially for real indoor environment simulation. Moreover, in the analysis of indoor channels, the dispersion characteristics of concrete walls should be modeled carefully and accurately for full wave simulation that it can effectively avoid the computational error caused by the dispersion of the ultra‐wideband (UWB) signal 22 . As we know, the auxiliary differential equation (ADE) approach combined with FDTD method has the capability of building corresponding models according to various media, providing a more common and flexible implementation for dispersive media 23–25 .…”
Section: Introductionmentioning
confidence: 99%